Association between obesity and depression among women in Indonesia: A questionnaire based study - Susi Ari Kristina; Nur Aini Mardea; Suci Hanifah (Journal of Global Pharma Technology, 2020)
Obesity is a global public health issue and the prevalence of obesity is growing worldwide every year. Studies have been performed since the early 1970s on the association between obesity and depression or other psychological disorders. In Indonesia, however, only a small number of studies have been carried out. The aim of this study was to examine whether obesity was associated with depression in a sample of women with overweight and obesity based on their BMI, anti-obesity treatment experience, and age among women in one province in Indonesia. Women aged 18 years and older who were selected from fitness centers in urban area of Yogyakarta province and self-reported BMI categorized as overweight and obese were eligible to participate. Voluntary participation in study survey was consented. A set of questionnaire consisting demographic characteristics and depression symptoms was developed and validated. Depression was assessed by the Patient Health Questionnaire-9 (PHQ-9), with a score of ≥10 used to indicate severe depression. Respondents who classified as overweight mostly had minimal depression level (33.58%) and none had severe depression level, whereas respondents who classified as obese mostly had moderate depression level (44.74%) and 3.95% had severe depression level. This study found that BMI, experience of using anti-obesity drugs, and age of respondents were significantly affected PHQ-9 score. Thus, these factors determined the level of depression among women surveyed. The study reported significant association between obesity and depression among women. This association depends on BMI, anti-obesity treatment experience, and age variables. Approaches to public health to reduce the burden of obesity or depression have to consider the strong link between these two common conditions.